Bis[4-(2-hydroxybenzylamino)phenyl] ether - Qi-Tao Liu; Xiao-Yan Zhang; Xiang-Dong Zhang; Chun-Hua Ge; Ya-Nan Guo (Acta Crystallographica Section E, 2008)
The title compound, C26H24N2O3, was synthesized by reduction of the corresponding Schiff base. The molecule does not possess crystallographic or non-crystallographic symmetry. The dihedral angle between the oxygen-bridged benzene rings is 67.98 (8)°. Both hydroxyl groups are involved in O—H...O intramolecular hydrogen bonding. The molecules are linked into a two-dimensional network parallel to the (010) plane by N—H...O hydrogen bonds.